Continent-wide releases of neotropical phytoseiids against the exotic cassava green mite in Africa - Yaninek, J.S.; Onzo, A.; Ojo, J.B. (1993)
Since the initiation of the classical biological control campaign by the International Institute of Tropical Agriculture to control the exotic mite, Mononychellus tanajoa, 11 species (18 distinct populations) of neotropical phytoseiids have been selected and shipped to Africa for experimental releases. Initially, natural enemies were selected because of their abundance and frequency on cassava. Between 1984 and 1988, more than 5.2 million phytoseiids belonging to 7 species of Colombian origin were imported to Africa and released in 348 sites in 10 countries. None of these species and populations ever became established in the wide range of agronomic and ecological conditions tested, apparently because of inadequate alternative food sources when M. tanajoa densities were low and extended periods of low relative humidity. Foreign exploration was adjusted in 1988 to focus on Neotropical regions that were agrometeorologically homologous to areas in Africa where the potential for severe M. tanajoa damage exists. Natural enemies associated temporally and spatially with M. tanajoa and capable of surviving periods of low M. tanajoa densities on alternative food sources in the new exploration sites were given selection priority. Several natural enemy candidates were immediately identified in Northeast Brazil and shipped to Africa. Approximately 1.9 million phytoseiids of the species Neoseiulus idaeus and Typhlodromalus limonicus of Brazilian origin were released in 133 sites in 6 countries in 1989 and 1990. N. idaeus has since become established in Benin, while T. limonicus may be established in Benin, Burundi, and Ghana.